Does increasing the severity of penalties assessed in association with the "zero tolerance for head contact" policy translate to a reduction in head impact rates in youth ice hockey? - Williamson, R. A.; Kolstad, A. T.; Nadeau, L.; Goulet, C.; Hagel, B.; Emery, C. A. (Clinical Journal of Sport Medicine, 2022)
Objective: The risk of concussion is high in Canadian youth ice hockey. Aiming to reduce this burden, in 2011, Hockey Canada implemented a national "zero tolerance for head contact (HC)" policy mandating the penalization of any player HC. In 2018 to 2020, Hockey Canada further amended this HC policy including stricter enforcement of severe HCs. This study aimed to compare HC rates, head impact location, and HC enforcement prepolicy, postpolicy, and after policy amendments in elite U15 Canadian youth ice hockey. Design: This is a prospective cohort study. Setting: A collection of events with the video camera located at the highest point near center ice in public ice hockey arenas in Calgary, Alberta. Participants:A convenience sample of 10 AA U15 games prepolicy (2008-2009), 8 games postpolicy (2013-2014), and 10 games after policy amendments (2020-2021). Independent Variables: An analysis of 3 cohort years regarding the HC-policy implementation and amendments. Main Outcome Measures: Using Dartfish video-analysis software, all player contacts and HCs [direct (HC1), indirect (eg, boards, ice) (HC2)] were tagged using validated criteria. Univariate Poisson regression clustering by team-game offset by game length (minutes) was used to estimate incidence rates (IR) and incidence rate ratios (IRR) between cohorts. Results: With additional rule modifications, a 30% reduction in HC1s emerged (IRR2013-2020 = 0.70, 95% CI, 0.51-0.95). Since the HC-policy implementation, HC1s decreased by 24% (IRR2008-2020 = 0.76, 95% CI, 0.58-0.99). The proportion of HC1s penalized was similar across cohorts (P2008-2009 = 14.4%; P2013-2014 = 15.5%; P2020-2021 = 16.2%). Conclusions: The HC-policy amendments have led to decreased HC1 rates. However, referee enforcement can further boost the HC-policy effectiveness. These findings can help future referee training and potential rule modifications to increase player safety nationally.